Safety and Efficacy of Contemporary Drug-Eluting Stents in Patients With ST-Segment Elevation Myocardial Infarction and a High Ischemic Risk - Lee, Oh-Hyun; Kim, Yongcheol; Son, Nak-Hoon; Cho, Deok-Kyu; Kim, Jung-Sun; Kim, Byeong-Keuk; Choi, Donghoon; Hong, Myeong-Ki; Jeong, Myung Ho; Jang, Yangsoo (Frontiers in Cardiovascular Medicine, 2022)
Background In patients with ST-elevation myocardial infarction (STEMI) with a high risk of ischemic events, the safety and efficacy of drug-eluting stent (DES) are unclear. Methods Based on the nationwide, multicenter, prospective registry, we selected 1,592 patients who underwent primary percutaneous coronary intervention (PCI) with everolimus-(EES) and zotarolimus-eluting stent (ZES) for STEMI with a high risk of an ischemic event. The occurrence of target lesion failure (TLF) for 3 years, defined as the composite of cardiac death, target vessel myocardial infarction (TV-MI), and ischemia-driven target lesion revascularization (ID-TLR), was evaluated. Results The prevalence of high ischemic risk features was observed in 43.4% (2,744/6,325) of overall patients with STEMI. Among them, a total of 1,078 and 514 patients were treated with EES and ZES, respectively. At 3 years, the risk of TLF was not significantly different between the two groups (p = 0.93). In addition, the incidence of cardiac death, TV-MI, ID-TLR, and definite/probable stent thrombosis (ST) were also not different between the two groups. Moreover, elderly patients (age > 75 years) and PCI for the left main disease were identified as independent predictors of TLF. Conclusion Implantation of EES or ZES provided comparable clinical outcomes in STEMI patients and high ischemic risks.